Survival Benefit of Adjuvant Radiotherapy: An Analysis of Low-Stage Invasive Ovarian Mucinous Carcinomas. Issue 9 (November 2017) - Kumar, Aalok; Le, Nhu; Gilks, C. Blake; Santos, Jennifer L.; Wong, Frances; Swenerton, Kenneth; Hoskins, Paul J.; McAlpine, Jessica N.; Tinker, Anna V.
Abstract : Objective: Our aim was to evaluate the population-based outcomes of stages I and II invasive ovarian mucinous carcinomas (MCs) treated with adjuvant platinum-based chemotherapy and abdominopelvic radiotherapy (XRT). Methods: International Federation of Gynecology and Obstetrics stage I/II MC cases referred to the British Columbia Cancer Agency between 1984 and 2014 were reviewed. Chemotherapy (minimum of 3 cycles) and XRT were the institutional policy for stages IA/B (grade 2/3) and IC/II (any grade). Physician patterns of practice determined XRT use in eligible patients, allowing for the comparison of outcomes based on receipt of XRT treatment on disease-free survival (DFS) and overall survival (OS). Results: We identified 129 patients. Univariate analyses on substages IA, IC no rupture, IC with intraoperative rupture, and IC with preoperative rupture demonstrated 10-year DFS rates of 67%, 67%, 67%, and 27% ( P = 0.004), respectively, and OS rates of 72%, 72%, 67%, and 38% ( P = 0.01), respectively. For all patients, adjuvant XRT demonstrated improved 10-year DFS (78% vs 36%, P = 0.05) and OS (83% vs 36%, P = 0.02). Subgroup analysis did not detect a benefit of adjuvant therapy for stage IA grade 1/2. Multivariate analysis confirmed the benefit of XRT on DFS (hazard ratio, 0.14; 95% confidence interval, 0.02–0.98; P = 0.047) and a trend to improved OS (hazard ratio, 0.12; 95% confidence interval, 0.009–1.64; P = 0.11), whereas decision tree analysis demonstrated a reduced rate of relapse (33% vs 77%) and death (20% vs 46%) with the use of XRT, exclusive of patients with preoperative rupture. Conclusions: This population-based retrospective study is the first to demonstrate that the use of adjuvant abdominopelvic XRT after chemotherapy can improve survival in patients diagnosed as having stage I/II MC. Patients with stage IA grade 1 and grade 2 MC can have adjuvant therapy omitted. Abstract : Supplemental digital content is available in the text.